2017
DOI: 10.1093/inthealth/ihx003
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prescribing for acute respiratory infections in children in Jordan

Abstract: Antibiotic prescribing is high and often inappropriate. Predictors of broad-spectrum antibiotic prescribing were identified. Health policy initiatives should involve all stakeholders to minimize inappropriate antibiotic prescription and to prevent poor outcomes associated with such practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
3
23
1
4
Order By: Relevance
“…This result may attributed to low pharmaceutical care interventions, physicians poor adherence to the guidelines, and absence of clinical decision support system in the operated computerized physician order entry system (CPOE) . Our findings are in line with other studies in Jordan that indicated high rate of DDIs and poor adherence to the guidelines by physicians (21,22,27). The difference between the recent studies in Jordan and our study is that the patient group in our research is highly vulnerable to severe deadly complications, and thus urgent precautionary measures are necessary.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result may attributed to low pharmaceutical care interventions, physicians poor adherence to the guidelines, and absence of clinical decision support system in the operated computerized physician order entry system (CPOE) . Our findings are in line with other studies in Jordan that indicated high rate of DDIs and poor adherence to the guidelines by physicians (21,22,27). The difference between the recent studies in Jordan and our study is that the patient group in our research is highly vulnerable to severe deadly complications, and thus urgent precautionary measures are necessary.…”
Section: Discussionsupporting
confidence: 89%
“…However, a recent study indicated that CKD is highly underdiagnosed in Jordan (19). Physicians in Jordan demonstrated poor adherence to current practice guidelines for safe prescription of antibiotics (20)(21)(22)(23), proton pump inhibitors (24,25), and non-steroidal antiinflammatory drugs (26). In addition, high rate of major and moderate drug-drug interactions was found among elderly patients in Jordan (27).…”
Section: Introductionmentioning
confidence: 99%
“…Most antibiotic prescriptions are provided in outpatient care, with respiratory tract infections being the most common diagnoses 3. Studies have shown that up to 78% of patients are prescribed antibiotics for respiratory tract infections in primary care, even though an estimated 90% are viral in aetiology and thus antibiotics are seldom required 4–8. Indeed, unless pneumonia is suspected, the effect of antibiotic treatment is moderate at best indicating that many antibiotic prescriptions are provided unnecessarily and without any overall patient benefit 9.…”
Section: Introductionmentioning
confidence: 99%
“…параты в педиатрии, и большая часть назначений прихо-дится именно на ОРВИ (78,4%), что под собой не имеет никакой основы [5,6].…”
Section: бронхопульмонология и лорunclassified
“…При этом необоснованная антибактериальная нагруз-ка приходится достоверно чаще на детей до 5 лет, в основном с ОСО и ОТ, в отличие от пациентов с лихорад-кой и более старшего возраста (6-12 лет) [5,7].…”
Section: бронхопульмонология и лорunclassified